The Paradox of Patriarchy: Men’s Vulnerabilities in the Tharu Community of Nepal - Nepali, Purna Bahadur (Journal of Gurubaba, 2024)
The patriarchal social system has been recognized widely as a privilege for men, their negative effects on them remained under discussion which was generally not researched. This study, therefore examines the paradox of patriarchy through applying a mixed-methods of investigation of men's life experiences in Nepal’s Tharu community. Combining survey data (n=80), focus group discussions (n=21), and key informant interviews (n=4), the research reveals how patriarchal norms simultaneously empower and constrain men. Findings indicate that men benefit from decision-making authority (75%) and property ownership (70%), but face significant vulnerabilities: 64% suppress emotions to avoid appearing "unmasculine," 59% endure stress as primary breadwinners, and 46% work in hazardous conditions, often as migrant laborers. Notably, 55% engage in physical violence to demonstrate masculinity, while institutional support remains scarce 50% perceive legal systems as discriminatory, and 35% report no access to mental health services. The study contributes to masculinities literature by documenting how patriarchal structures harm men in South Asia, challenging binary narratives of male privilege. Practical implications include recommendations for gender-inclusive policies and community-based psychosocial interventions targeting men’s unmet needs.